The effect of carbohydrate meals with high or low glycemic index on blood glucose concentration following prolonged strenuous exercise - J. Ziaolhagh; S. Choobineh; A.A. Gaeini; M. Alizadeh; M. Arab (Afarand Scholarly Publishing Institute, 2012)
Introduction : The glycemic index (GI) is a system for the classification of carbohydrate-containing foods that is based on their blood-glucose-raising potential. In addition, Carbohydrate ingestion following prolonged strenuous exercise attenuates the suppression of immune system by maintaining plasma glucose concentration and minimizing stress hormone and inflammatory cytokines responses that is the most important factor in reduction of inflammation in paralyzed athletes.   Purpose: The purpose of this study was to determine the effect of pre-exercise high carbohydrate meals with high or low glycemic index on glucose profile pre, immediately post and 1 hour after subsequent endurance exercise.   Methods & Matherials : in a semi-empirical double-blind trial, 12 male athletes was purposefully selected to be titled triable and then divided in 2 groups of high (HGI=94) and low glycemic index (LGI=40), in amount of 1 gram per kilogram of body weight. Afterwards, they performed two 90-min running on a treadmill at 70% VO2max for 2 hours Within 7 days. Blood samples were collected before, immediately after and 1 hour after run for measure of blood glucose concentrations.   Results : Plasma glucose concentrations were significantly higher in LGI than HGI immediately after exercise (p=0.001). However, there were no significant differences in plasma glucose pre-exercise (p=1.000) and 1 hour post exercise (p=0.318) concentrations between trials.   Conclusion : Ingestion of a LGI meal 2 h before sub maximal exercise maintains plasma glucose concentration during subsequent exercise when compared with ingestion of a HGI meal and it seemed to be useful in diet planning of paralyzed athletes.